OECS INFONET and OLA development policy - Primus, Wilma (OECS St. John'sAG, 1996)
Focuses on issues such as management policy; services policy; pricing policy for products and services; commercial policy; information technology policy and reclassification; in the context of global network developments. Identifies key issues and policy initiatives which could bring INFONET services closer to global realities.